ANALISIS KEKERASAN PERLAKUAN PANAS BAJA PEGAS DENGAN PENDINGINAN SISTEM PANCARAN PADA TEKANAN 20, 40 DAN 60 PSi - Asfarizal Asfarizal; Suhardiman Suhardiman (Jurnal Teknik Mesin (JTM), 2012)
In the heat treatment with rapid dye method (Quenching) has the disadvantage that the increase of water temperature around the metal is high enough, it is not suitablefor long material, this issue need another attempt to study the cooling method with spraying system which is done to the spring steel. Heating is done until temperature of 920 ° C, with holding time 60 min, pressure 20, 40, 60 psi and 120 seconds of spraying time. After heat treatment, the specimens' hardness is tested by the method of Rockwell C (HRC). The results of hardness testing showed that the average hardness at a pressure of 20, 40, 60 psi is 34.55 HRC, HRC 39.80, and 40.45 HRC. At a pressure of 60 psi martensiticphase is observed clearly. There is a tendency that the higher the pressure, the hardness increased.